Does Autologous Transfusion Decrease Allogeneic Transfusion in Liposuction Surgery of Lymphedema Patients? - Chen, Linfeng; Chang, Kun; Chen, Yan; Xu, Zhenhua; Shen, Wenbin (Frontiers in Medicine, 2022)
Background and objective: Liposuction is an effective treatment for fat disposition in lymphedema. Blood transfusion has been seldom investigated in lymphedema liposuction surgery. The purpose of the study was to analyze clinical factors associated with blood transfusion in liposuction surgery of lymphedema patients, and compare the autologous and allogeneic transfusion patterns. Methods: A total of 1187 cases of liposuction due to lymphedema were recruited. Demographic, laboratory tests and operation information were collected. Patients were divided into transfusion and non-transfusion groups which two patterns were compared and analyzed. Results: Between the two group, there is a significant difference of post-operative hemoglobin levels, as well as gender, age, surgery duration, body weight change, intra-operative transfusion volume and blood loss, hospital length of stay, and surgical site distribution. There is a significant difference in the comparison of hospital stay length, autologous transfusion volume, combined allogeneic volume, operative blood loss, intra-operative transfusion volume, change of hemoglobin levels between predonation and acute normovolemic hemodilution (ANH) transfusion. In comparison with the allogeneic transfusion only patients, the mean allogeneic transfusion volume in either ANH group, predonated transfusion group, or mixed group is statistically lower. Allogeneic transfusion volume in the predonated only group is significantly lower than that of either the ANH only group or the mixing ANH with pre-donation group. Ordinary least squares regression analysis suggests that autologous transfusion in the ANH only mode is statistically associated with allogeneic transfusion. Conclusions: This study described the blood transfusion in lymphedema liposuction surgery, and compared autologous and allogeneic transfusion patterns in these patients. Autologous transfusion can reduce the transfusion volume of allogeneic blood, and might be a beneficial mode of transfusion in these patients.